Sosialisasi Bahaya Gadget (Handphone) Bagi Anak-Anak Di Desa Air Petai Kecamatan Sukaraja Kabupaten Seluma, Bengkulu - Devi, Made Tiara; Anggriani, Ida; Susanti, Neri; Febliansa, Rahman; Indriasari, Nia (Jurnal Dehasen Mengabdi, 2024)
The use of information and communication technology in the world of education today is growing, one of them is the gadget (phone). Gadgets (phone) is one of the forms of information technology and communication that is constantly evolving from time to time. Excessive use of gadgets (mobiles) in children can have a negative impact on the growing children of primary school age, it does not exclude the possibility that will cause children to become personal closure due to the lack of social interaction. However, on the other hand, the use of information and communication technology is very beneficial for learning activities. In this case, it is necessary to have sufficient knowledge of the technology and how it is applied in everyday life. In this case, parental supervision is essential, because elementary school children usually have a high level of curiosity for new things.